Genome Sequencing Reveals the Potential of Achromobacter sp. HZ01 for Bioremediation - Hong, Yue-Hui; Ye, Cong-Cong; Zhou, Qian-Zhi; Wu, Xiao-Ying; Yuan, Jian-Ping; Peng, Juan; Deng, Hailin; Wang, Jiang-Hai (Frontiers in Microbiology, 2017)
Petroleum pollution is a severe environmental issue. Comprehensively revealing the genetic backgrounds of hydrocarbon-degrading microorganisms contributes to developing effective methods for bioremediation of crude oil-polluted environments. Marine bacteriumc Achromobacter sp. HZ01 is capable of degrading hydrocarbons and producing biosurfactants. In this study, the draft genome (5.53 Mb) of strain HZ01 was obtained by Illumina sequencing, containing 5,162 predicted genes. Genome annotation showed that “amino acid metabolism” was the most abundant metabolic pathway. Strain HZ01 is not capable of using some common carbohydrates as the sole carbon sources, which is due to that it contains few genes associated with carbohydrate transport and lacks some important enzymes related to glycometabolism. It contains abundant proteins directly related to petroleum hydrocarbon degradation. AlkB hydroxylase and its homologs were not identified. It harbors a complete enzyme system of terminal oxidation pathway for n-alkane degradation, which may be initiated by cytochrome P450. The enzymes involved in the catechol pathway are relatively complete for the degradation of aromatic compounds. This bacterium lacks several essential enzymes for methane oxidation, and Baeyer-Villiger monooxygenase involved in the subterminal oxidation pathway and cycloalkane degradation was not identified. These results suggest that strain HZ01 degrades n-alkanes via the terminal oxidation pathway, degrades aromatic compounds primarily via the catechol pathway and can not perform methane oxidation or cycloalkane degradation. Additionally, strain HZ01 possesses abundant genes related to the metabolism of secondary metabolites, including some genes involved in biosurfactant (such as glycolipids and lipopetides) synthesis. The genome analysis also reveals its genetic basis for nitrogen metabolism, antibiotic resistance, regulatory responses to environmental changes, cell motility, and material transport. The obtained genome data provide us with a better understanding of hydrocarbon-degrading bacteria, which may contribute to the future design of rational strategies for bioremediation of petroleum-polluted marine environments.